Neurometabolic Diagnosis in Children who referred as Neurodevelopmental Delay (A Practical Criteria, in Iranian Pediatric Patients) - KARIMZADEH, Parvaneh; JAFARI, Narjes; NEJAD BIGLARI, Habibeh; JABBEHDARI, Sayena; KHAYAT ZADEH, Simin; AHMAD ABADI, Farzad; LOTFI, Azra (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Karimzadeh P, Jafari N, Nejad Biglari H, Jabbehdari J, Khayat Zadeh S, Ahmad Abadi F, Lotfi A. Neurometabolic Diagnosis in Children who referred as Neurodevelopmental Delay (A Practical Criteria, in Iranian Pediatric Patients). Iran J Child Neurol. Summer 2016; 10(3):73-81. Objective We aimed to investigate the clinical and para clinical manifestations of neuro metabolic disorders, in patients who presented by neuro developmental delay in their neuro developmental milestones. Materials & Methods The patients diagnosed as neuro developmental delay and regression with or without seizure at the Neurology Department of Mofid Children Hospital in Tehran, Iran between 2004 and 2014 were included in our study. These patients diagnosed as neuro developmental delay by pediatric neurologists in view of diagnostic /screening neuro developmental assessment tests. The patients who completed our inclusion criteria as neuro metabolic disorders were evaluated in terms of metabolic and genetic study in referral lab. Results Overall, 213 patients with neurometabolic disorders were diagnosed. 54.3% of patients were male. The average age of patients was 41 +-46.1 months. 71.4% of parent’s patients had consanguinity of marriages. Eighty seven percent of patients had developmental delay (or/and) regression. 55.5% of them had different type of seizures. Overall, 213 patients with 34 different neurometabolic disorders were diagnosed and classified in the 7 sub classes, consisting of: 1- organic acidemia and aminoacidopathy (122 patients), 2-storage disease (37 patients) 3- eukodystrophy (27 patients), other classes consisted: lipid oxidation disorders, urea cycle disorders, progressive myoclonic epilepsy; and peroxizomal disorders (27 patients). Conclusion In patients with developmental delay or regression, with or without seizure, abnormal neurologic exam along with positive family history of similar disorder or relative parents, abnormal brain imaging with specific patterns, neurometabolic disorders should be considered as one of the important treatable diseases. References Brismar J. CT and MRI of the brain in inherited neurometabolic disorders. J Child Neurol 1992 Apr;7 Suppl:S112-31. Barkovich AJ. An approach to MRI of metabolic disorders in children. J Neuroradiol 2007; 34(2):75-88. Barkovich AJ. A magnetic resonance approach to metabolic disorders in childhood. Rev Neurol 2006 10;43 Suppl 1:S5-16. Zimmerman RA. Neuroimaging of inherited metabolic disorders producing seizures. Brain Dev 2011;33(9):734-44. Cakir B, Teksam M, Kosehan D, Akin K, Koktener A.Inborn errors of metabolism presenting in childhood. J Neuroimaging 2011;21(2):e117-33. Burton BK. Inborn errors of metabolism in infancy: a guide to diagnosis. Pediatrics 1998;102(6):E69. Iman G. Mahmoud M, Marwa M, Miral R, Marian G, Nevin W, Ameera E. Clinical, Neuroimaging, and Genetic Characteristics of Megalencephalic Leukoencephalopathy With Subcortical Cysts in Egyptian Patients. Pediatr Neurol 2014;140e-148. Sarar M, Ebtessam M, Melegy B, Iman T, Amany H, Khaled K. Neurometabolic Disorders-Related Early Childhood Epilepsy: A Single-Center Experience in Saudi Arabia. Pediatr Neurol 2015; xx, 1e9. Talebian A, Jahangiri M, Rabiee M, Masoudi N, Akbari H, Sadat Z. The Etiology and Clinical Evaluations of Neonatal Seizures in Kashan, IRAN. Iran J Child Neurol 2015;9(2):29-35. Vigevano F, Bartuli A. Infantile epileptic syndromes and metabolic etiologies. J Child Neurol 2002;17:3S9e13. Karimzadeh P. Approach to Neurometabolic Diseases from a Pediatric Neurological Point of View. Iran J Child Neurol 2015;9(1): 1-16. Hee Eun S, Houn Hahn S. Metabolic evaluation of children with global developmental delay. Korean J Pediatr 2015;58(4):117-122. Kroll R, Pagel M, Roman S, Barkovich A, D’Agostino A, Neuwelt E.White matter changes associated with feline GM2 gangliosidosis (Sandhoff disease): correlation of MR findings with pathologic and ultrastructural abnormalities. Am J Neuroradiol 1995;16(6):1219-26. Karimzadeh P, Jafari N, Nejad Biglari H, Jabbeh Dari S, Ahmad Abadi F, Alaee M,. GM2-Gangliosidosis (Sandhoff and Tay Sachs disease): Diagnosis and Neuroimaging Findings (An Iranian Pediatric Case Series). Iran J Child Neurol 2014;8(3):55-60. Wang Q, Ding Y, Liu Y, Li X, Wu T, Song J, et al.(Clinical and laboratory studies on 28 patients with glutaric aciduria type 1). Zhonghua Er Ke Za Zhi 2014 Jun;52(6):415-9. Karimzadeh P, Pirzadeh Z, Ahmadabadi F, Jafari N, Jabbehdari S, Nemati H,. Glutaric aciduria type 1: diagnosis and neuroimaging findings of this neurometabolic disorder in an Iranian pediatric case series. Int J Develop Dis 2014; 60(3): 1–6 Weller S, Rosewich H, Gärtner J. Cerebral MRI as a valuable diagnostic tool in Zellweger spectrum patients. J Inherit Metab Dis 2008;31(2):270-80. Groeschel S, Kehrer C, Engel C, I Dali C, Bley A, Steinfeld R, et al. Metachromatic leukodystrophy; natural course of cerebral MRI changes in relation to clinical course. J Inherit Metab Dis 2011;34(5):1095-102. Klee D, Thimm E, Wittsack HJ, Schubert D, Primke R, Pentang G,et al. Structural white matter changes in adolescents and young adults with maple syrup urine disease. J Inherit Metab Dis 2013;36(6):945-53. Karimzadeh P. Approach to neurometabolic diseases from a pediatric neurological point of view. Iran J Child Neurol 2015;9(1):1-16. Leuzzi V1, Tosetti M, Montanaro D, Carducci C, Artiola C, Carducci C,et al. The pathogenesis of the white matter abnormalities in phenylketonuria. A multimodal 3.0 tesla MRI and magnetic resonance spectroscopy (1H MRS) study. J Inherit Metab Dis 2007;30(2):209-16. Epub 2007 Jan 23. Karimzadeh P, Ahmadabadi F, Jafari N, Shariatmadari F, Nemati H, Ahadi A, Karimi Dardashti S, Mirzarahimi M, Dastborhan Z, Zare Noghabi J. Study on MRI changes in phenylketonuria in patients referred to mofid hospital/ iran. Iran J Child Neurol 2014 ;8(2):53-6. Abdelhalim AN, Alberico RA, Barczykowski AL, Duffner PK. Patterns of magnetic resonance imaging abnormalities in symptomatic patients with Krabbe disease correspond to phenotype. Pediatr Neurol 2014;50(2):127-34. Santosh Rai PV, Suresh BV, Bhat IG, Sekhar M, Chakraborti S.Childhood adrenoleukodystrophy - Classic and variant - Review of clinical manifestations and magnetic resonance imaging. J Pediatr Neurosci 2013;8(3):192-7. George U, Varte N, Rathore S, Jain V, Goyal S. “Split thalamus”: Internal medullary involvement in Wilson’s disease. Neurol India 2010;58:680 Oder W, Prayer L, Grimm G, Spatt J, Ferenci P, Kollegger H, et al. Wilson’s disease: evidence of subgroups derived from clinical findings and brain lesions. Neurology 1993;43:120-4. Bickel H.(Brain atrophy and disorders of the amino acid metabolism). Monatsschr Kinderheilkd 1967;115(4):254-8. Karimzadeh P, Jafari N, Alai M, Jabbehdari S, Nejad Biglari H. Homocystinuria: Diagnosis and Neuroimaging Findings of Iranian Pediatric patients. Iran J Child Neurol 2015;9(1):94-8. Sreenivasan P, Purushothaman KK.Radiological clue to diagnosis of Canavan disease. Indian J Pediatr 2013;80(1):75-7. Karimzadeh P, Jafari N, Nejad Biglari H, Rahimian E, Ahmadabadi F, Nemati H, Nasehi MM, Ghofrani M, Mollamohammadi M. The Clinical Features and Diagnosis of Canavan’s Disease: A Case Series of Iranian Patients. Iran J Child Neurol 2014 ;8(4):66-71. Nguyen HV, Ishak GE. Canavan disease - unusual imaging features in a child with mild clinical presentation. Pediatr Radiol 2014 Aug 9. Rogers T, al-Rayess M, O’Shea P, Ambler MW.Dysplasia of the corpus callosum in identical twins with nonketotic hyperglycinemia. Pediatr Pathol 1991;11(6):897-902. Johnson JA, Le KL, Palacios E.Propionic acidemia: case report and review of neurologic sequelae. Pediatr Neurol 2009;40(4):317-20. Karimzadeh P, Jafari N, Ahmad Abadi F, Jabbedari S, Taghdiri MM, Alaee MR, Ghofrani M, Tonekaboni SH, Nejad Biglari H. Propionic acidemia: diagnosis and neuroimaging findings of this neurometabolic disorder. Iran J Child Neurol 2014;8(1):58-61. 35.Desai S, Ganesan K, Hegde A.Biotinidase deficiency: a reversible metabolic encephalopathy. Neuroimaging and MR spectroscopic findings in a series of four patients. Pediatr Radiol 2008;38(8):848-56. Karimzadeh P, Ahmadabadi F, Jafari N, Jabbehdari S, Alaee MR, Ghofrani M, Taghdiri MM, Tonekaboni SH. Biotinidase deficiency: a reversible neurometabolic disorder (an Iranian pediatric case series). Iran J Child Neurol 2013;7(4):47-52. Brismar J, Ozand PT.CT and MR of the brain in disorders of the propionate and methylmalonate metabolism. Am J Neuroradiol 1994;15(8):1459-73. Karimzadeh P, Jafari N, Ahmad Abadi F, Jabbedari S, Taghdiri MM, Nemati H, Saket S, Shariatmadari SF, Alaee MR, Ghofrani M, Tonekaboni SH. Methylmalonic acidemia: diagnosis and neuroimaging findings of this neurometabolic disorder (an Iranian pediatric case series). Iran J Child Neurol 2013;7(3):63-6.